Neutrophil Recruitment in Pneumococcal Pneumonia - Palmer, Catherine S.; Kimmey, Jacqueline M. (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus pneumoniae (Spn) is the primary agent of community-acquired pneumonia. Neutrophils are innate immune cells that are essential for bacterial clearance during pneumococcal pneumonia but can also do harm to host tissue. Neutrophil migration in pneumococcal pneumonia is therefore a major determinant of host disease outcomes. During Spn infection, detection of the bacterium leads to an increase in proinflammatory signals and subsequent expression of integrins and ligands on both the neutrophil itself as well as endothelial and epithelial cells. These integrins and ligands mediate the tethering and migration of the neutrophil from the bloodstream to the site of infection. A gradient of host-derived and bacterial-derived chemoattractants contribute to targeted movement of neutrophils. During pneumococcal pneumonia, neutrophils are rapidly recruited to the pulmonary space, but studies show that some of the canonical neutrophil migratory machinery is dispensable. Investigation of neutrophil migration is necessary for us to understand the dynamics of pneumococcal infection. Here, we summarize what is known about the pathways that lead to migration of the neutrophil from the capillaries to the lung during pneumococcal infection.